Decoding Virtual Employee Engagement: A Bibliometric Analysis - Pringgabayu, Dematria; Disman, Disman; Rofaida, Rofi (Ekonomis: Journal of Economics and Business, 2024)
This study investigates virtual employee engagement using a bibliometric analysis methodology. The objective of this study is to collect information and data pertinent to virtual employee engagement. In conducting this study, the researcher collected and extracted data from the Scopus database. In July 2023, a total of 933 articles were discovered in the Scopus database. After that, VOSviewer is used for scientific mapping and analysis of publication performance, including identifying the contributions of authors, journals, countries, and the number of author keywords. The quantity of publications has increased significantly over the years. Several countries have contributed to publications on virtual employee engagement. The United States contributes the most to this publication subject, followed by India, the United Kingdom, Australia, China, Malaysia, the Netherlands, Germany, Pakistan, and France. Based on article documents production, the Personnel Review" is the journal with the greatest influence because it produces 32 documents. While, the highest value number of citations is "International Journal of Human Resource Management" with the total number of 1.015 citations. In the field of virtual employee engagement research, De Clercq D and Pereira R is regarded as the highest number of document publication author; and Knight C, Patterson M, et al. are the most cited authors with 297 citations. The keyword presents key terminology from the field organized into six distinct categories colors (red, blue, green, yellow, purple and light blue). This study has a broad implication for virtual employee engagement perceptions. The findings can benefit many researchers to can utilize the data for their investigations with depth of information encourages field research.